Complexity of a complex disease; understanding genes, environment and immunity in rheumatoid arthritis development. Issue 5 (October 2007) - Ronninger, Marcus; Käällberg, Henrik; Lundströöm, Emeli; Lindahl, Annmarie; Klareskog, Lars; Alfredsson, Lars; Padyukov, Leonid
Rheumatoid arthritis (RA) is a severe and common inflammatory disease with unclear etiology, but is likely to be precipitated and modulated by complex interactions between genetic and environmental factors. Efficient prevention or cure of RA has not yet been developed. Numerous attempts to understand the disease mechanisms and to suggest preventive measures have not been successful. Lately, defining major subtypes of RA by the presence of autoantibodies has been very productive when studying genetic and environmental risk factors for RA. The most replicated risk factors for RA are variations in the HLA-DRB1 gene and smoking and there is also evidence that there is a dose response relationship (i.e., greater number of cigarettes and longer duration of smoking are associated with increased risk of RA). However, these risk factors as well as their interaction have mainly been associated with anticitrullinated peptide antibodies and/or rheumatoid factor positive RA. More research is needed to identify the environmental triggers for the disease and, in context of gene––environment interaction, to define genetically homogenous risk groups where disease could be prevented by neutralizing these risk factors. This also calls for new efforts to delineate major pathways that can promote or counteract the development of rheumatoid arthritis.